2003
DOI: 10.1023/a:1025448908694
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Increased oxidative stress and reduction in antioxidant enzymes have been suggested to be involved in the pathophysiology of congestive heart failure subsequent to myocardial infarction (MI). The objective of the present study was to characterize changes in the mRNA abundance and protein levels for the enzymatic antioxidants, superoxide dismutase (SOD), glutathione peroxidase (GSHPx) and catalase during the sequelae of congestive heart failure in rats. MI was produced by the ligation of the left coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The mechanisms for the changes in SOD levels in the repairing kidney remain to be elucidated. Studies have shown that SOD is decreased in the repairing heart and kidney [23, 24]. Thus, renal oxidative stress in this model of hypertension is induced by both upregulated ROS production and reduced antioxidant enzyme in the kidney.…”
Section: Discussionmentioning
confidence: 93%
“…The mechanisms for the changes in SOD levels in the repairing kidney remain to be elucidated. Studies have shown that SOD is decreased in the repairing heart and kidney [23, 24]. Thus, renal oxidative stress in this model of hypertension is induced by both upregulated ROS production and reduced antioxidant enzyme in the kidney.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, we found to be a downregulation of SOD1 mRNA after MI procedures compared to control. SOD1 gene overexpression also elevated levels of myocyte catalase and mitochondrial GSH, which might also act together with SOD1 against oxidative stress (Khaper et al, 2003). Catalase gene was differently expressed in each procedure compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…Khaper et al . followed the expression of various antioxidant enzymes, including MnSOD, at different times following myocardial infarction in rats, and found that MnSOD mRNA levels were reduced early (1 week) and long after (16 weeks) infarction, but MnSOD mRNA was near control levels at 4 weeks post-infarction [356]. …”
Section: Implications For Diseasementioning
confidence: 99%